Dynamic Energy Conservation Based on Room Characteristics at Polytechnic State of Pontianak - Yunita; Mariana Syamsudin; Wendhi Yuniarto; Freska Rolansa (Journal of ICT, Design, Engineering and Technological Science, 2019)
Generally, energy conservation is carried out on a building as a whole, but in this research the energy conservation is carried out dynamically based on the characteristics and the user of the room. In this research, the lux measurement has been taken at certain times. Based on the characteristics of the existing room at Polytechnic State of Pontianak, the lux measurements were taken at one of the electronics laboratory, one technician room, electrical engineering department library, one classroom for information technology students and one academic staff office. These rooms divided into three size: small, medium, and large. The data that has been taken was compared with the standard of room lighting according to the Indonesian National Standard SNI-03-6917-2000. Analysis in determining lux can be used with fuzzy logic based on room size, number of lights and electrical power. Lux can be obtained by 3 values, namely weak, medium, and strong. With fuzzy it is obtained that the value of output membership for Lux strong for library = 0.11, technician room = 0.10, and classroom IT 7 = 0.31 with the scale of 0 – 1. With 0 is the value of the minimum and 1 is the maximum value of the fuzzy membership. It can be seen between the 3 rooms that classroom It 7 is the room with better lighting, hence better lux value.